Aprendizaje basado en proyectos en el desarrollo de competencias matemáticas del sexto grado de la Unidad Educativa “José Ángel Palacio”, Loja 2022-2023 - Villamagua León, Katty Jhomayra (2023)
This research deals with Project-based learning in the development of mathematical skills. Its general objective is to analyze the impact of project-based learning by building a methodological proposal for developing mathematical skills in sixth-grade students. To fulfill this objective, three specific goals were set. The first consisted of identifying the mathematical skills that students have acquired during the teaching-learning process. The second was to create a methodological proposal through project-based learning to develop and strengthen mathematical skills in students. Finally, the third is: Evaluate the impact of the project-based learning methodological proposal on developing and strengthening students' mathematical skills. To carry out this study, a descriptive type of research with a mixed approach was used. The design was non-experimental cross-sectional. In the development of the study, the methods described below were used: Inductive, deductive, statistical, analytical, and synthetic methods, and among the techniques are: survey, interview, and pre and post-evaluation. In the same way, the instruments that were used were: a questionnaire, a structured questionnaire, pre- and post-evaluative questionnaire for data collection. The population considered for the research was from the "José Ángel Palacio" public school. Through a simple probabilistic sampling, twenty-one students and one teacher were selected. Innovative methodologies such as Project-Based Learning are used since they allow students to be the axis of the process. Through research, it was possible to determine that project-based learning is a methodology that provides many benefits for mathematical skills to materialize, which is essential in learning development.